Campus talk : effective communication beyond the classroom. - Dushku, Silvana; Thompson, Paul, 1958- (Edinburgh University Press, 2021)
The first of two workbooks aimed at upper-intermediate and advanced learners of English (CEFR B1-C2) to promote interactional language awareness and develop active listening skills.